NUUK - Wagner Sørensen, Bo (Tidsskriftet Antropologi, 2003)
The article is based on 40 interviews from fieldwork in 2001 and 2002. It deals with Greenlanders’ views on the development of Nuuk, the capital of Greenland, and the relationship between Nuuk and the rest of Greenland. Contrary to the anti-urban narratives of the 1960s and 1970s, the informants – migrants and locals – like living in a relatively big town such as Nuuk, because it has much more to offer than the smaller places. Contrary to conventional beliefs about Greenlanders, the informants tend to regard social change as only natural and be oriented towards the present and the future rather than the past. Thus it is not a question of people merely surviving, but rather a question of people thriving, in the urban landscape of Nuuk. According to one of the informants, the rest of Greenland would likely be depopulated if the municipality of Nuuk would be able to solve its housing problems. Municipal housing problems, however, are part of the larger issue of regional development, which is highly political due to the legacy of the policy of centralization during the 1960s. This policy is usually associated with the Danish authorities and thus seen as antithetical to a proper Greenlandic policy.